Health education lecture method to increase posyandu cadres' knowledge about stunting prevention in children - Indrawati Aris Tyarini; Asridawati Akib; Fithri Ratnasari; Tunggul Sri Agus Setyaningsih; Ari Setyawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Stunting is a serious health problem in children, especially in developing countries. Sufficient knowledge about stunting prevention is essential for Posyandu cadres, as they play a role in providing information and support to mothers and children in the community. Objective: evaluate the effectiveness of the lecture method in increasing the knowledge of Posyandu cadres about stunting prevention in children. Method: This type of research uses a quantitative approach. In this study, using a group of health posyandu cadres, stunting knowledge was given using the lecture method. The population in the study of cadre mothers was 60 people, with a sample size of 36 people, using purposive sampling. Measuring instruments use questionnaire instruments and analysis results are in the form of descriptive data equipped with tables. Results: based on statistical test wilcoxon test Asymp.Sig. (2-tailed) P Value 0.000 ≤ 0.05 means that there is an increase in knowledge between before and after educational intervention with the lecture method. Conclusion: The lecture method is effective in increasing the knowledge of Posyandu cadres about stunting prevention in children. It is hoped that the results of this study can be the foundation for a broader health education program to overcome the problem of stunting in children in the community.